Preferensi Produk Perbankan Syariah, Di Kota Tarakan: Pendekatan Analisis Multigrup - Mohamad Nur Utomo; Rahmi Nur Islami; Adinda Pratiwi (Jurnal Ilmiah Ekonomi Islam, 2023)
This research stems from the phenomenon of the still low market share of Islamic banking compared to conventional banking in Indonesia. The study aims to examine the factors influencing preferences for Islamic banking products using exogenous variables including knowledge, trust, and the quality of Islamic banking product services, as well as demographic characteristics (gender and education level) as moderating variables. The research method employs SEM-PLS and Multigroup Analysis, with primary data collected from respondents of Islamic banks in Tarakan city, North Kalimantan. The research findings confirm that knowledge, trust, and the quality of product services positively enhance consumer preferences for Islamic banking products. Gender and education level are not moderators in the influence of knowledge, trust, and product service quality on consumer preferences for Islamic banking products. These research findings lend support to the consumer behavior theory that elucidates the process by which individuals decide which product becomes their primary preference in decision-making.